2020 IEEE International Conference on Robotics and Automation (ICRA) 2020
DOI: 10.1109/icra40945.2020.9197542
|View full text |Cite
|
Sign up to set email alerts
|

Design and Autonomous Stabilization of a Ballistically-Launched Multirotor

Abstract: Aircraft that can launch ballistically and convert to autonomous, free-flying drones have applications in many areas such as emergency response, defense, and space exploration, where they can gather critical situational data using onboard sensors. This paper presents a ballistically-launched, autonomously-stabilizing multirotor prototype (SQUID-Streamlined Quick Unfolding Investigation Drone) with an onboard sensor suite, autonomy pipeline, and passive aerodynamic stability. We demonstrate autonomous transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Several robotic hands have been developed by modifying existing underactuated designs in different ways to achieve translation and rotation of objects (Bouman et al, 2020;Morino et al, 2020). The GR2 gripper (Rojas et al, 2016) is a two-fingered hand that introduces an elastic pivot joint between the fingers to enlarge the range of planar reorientation.…”
Section: Add-on Designs For Increasing Dexterity Of Simple Grippersmentioning
confidence: 99%
“…Several robotic hands have been developed by modifying existing underactuated designs in different ways to achieve translation and rotation of objects (Bouman et al, 2020;Morino et al, 2020). The GR2 gripper (Rojas et al, 2016) is a two-fingered hand that introduces an elastic pivot joint between the fingers to enlarge the range of planar reorientation.…”
Section: Add-on Designs For Increasing Dexterity Of Simple Grippersmentioning
confidence: 99%
“…Ballistically deployable foldable RMs such as the one shown in Fig. 5b with passive, spring-loaded hinges at the rotor arms can successfully transition from the launch configuration to a fully controllable flight, opening up possibilities to investigate such launching approaches for MAVs in a variety of environments (Pastor et al 2019;Bouman et al 2020).…”
Section: Passive Foldable Rmsmentioning
confidence: 99%
“…In such scenarios, modeling and parameter uncertainties for other interaction tasks such as pulling objects by a tiltrotor RM significantly influence the tracking performance. In this context, robust control methods such as robust model reference controller have been successfully demonstrated that guarantee robustness not only to parametric and matched uncertainties, but also to unmatched uncertainties (Anderson et al 2020). The performance can further be improved by employing disturbance observers with sliding mode control (SMC) techniques where the output of the observer can be…”
Section: Llfc For Tiltrotor Rmsmentioning
confidence: 99%
“…Several aerial vehicles capable of changing shape have been previously developed. For example, in [1] a vehicle capable of automatically unfolding after being launched from tube is presented, and in [2] a vehicle is presented which uses foldable origami-style arms to automatically increase its wingspan…”
Section: A Related Workmentioning
confidence: 99%